2016
DOI: 10.1161/circulationaha.115.017443
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Blocks Cardiomyocyte Autophagic Flux by Inhibiting Lysosome Acidification

Abstract: Background The clinical use of doxorubicin is limited by cardiotoxicity. Histopathologic changes include interstitial myocardial fibrosis and appearance of vacuolated cardiomyocytes. Whereas dysregulation of autophagy in the myocardium has been implicated in a variety of cardiovascular diseases, the role of autophagy in doxorubicin cardiomyopathy remains poorly defined. Methods and Results Most models of doxorubicin cardiotoxicity involve intraperitoneal injection of high-dose drug, which elicits lethargy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
347
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(384 citation statements)
references
References 74 publications
31
347
2
4
Order By: Relevance
“…2D) and in intact hearts as assessed using fasted transgenic RFP-GFP-LC3 mice treated with bafilomycin A1 (Fig. 2E) (35). Together, these results indicate that adrenergic signaling and elevated signaling through FAK lead to a similar transient suppression of cardiac autophagy.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…2D) and in intact hearts as assessed using fasted transgenic RFP-GFP-LC3 mice treated with bafilomycin A1 (Fig. 2E) (35). Together, these results indicate that adrenergic signaling and elevated signaling through FAK lead to a similar transient suppression of cardiac autophagy.…”
Section: Resultsmentioning
confidence: 59%
“…Interestingly, there are striking parallels between challenged Beclin1 ϩ/Ϫ mice and SF2 mice. Both lines of mice exhibit preserved systolic function and reduced perivascular and interstitial fibrosis following I/R or doxorubicin treatment (7,26,27,35). Moreover, myocardial infarct size and myocyte apoptosis following I/R was significantly reduced in both models (8,26).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The number of yellow puncta in the merged channel represented the number of autophagosomes. The number of autolysosomes (as a result of autophagosome-lysosome fusion) were represented by the number of red puncta as described previously (42,43).…”
Section: Methodsmentioning
confidence: 99%
“…However, its clinical use is limited by potential cardiotoxicity. We and others have recently shown that autophagic flux is impaired in the mouse models of doxorubicin-induced cardiotoxicity, which contributes to heart injury [14][15][16]. Moreover, we have shown that IF is capable of restoring autophagic flux and ameliorating pathological alterations including increased cytoplasmic vacuolization, fibrosis, apoptosis and generation of reactive oxygen species in both acute and chronic doxorubicin cardiotoxicity [16].…”
Section: If and Doxorubicin-induced Cardiotoxicitymentioning
confidence: 72%